2017
DOI: 10.2196/jmir.7467
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions Regarding Use of Virtual Reality in Health Care: A Social Media Content Analysis Using Facebook

Abstract: Background Virtual reality (VR) technology provides an immersive environment that enables users to have modified experiences of reality. VR is increasingly used to manage patients with pain, disability, obesity, neurologic dysfunction, anxiety, and depression. However, public opinion regarding the use of VR in health care has not been explored. Understanding public opinion of VR is critical to ensuring effective implementation of this emerging technology. Objective This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…Our study found that a majority of orthoptists would be willing to incorporate virtual reality as a therapeutic tool for AMD patients if studies prove its effectiveness. This is in concordance with a 2017 survey by Keller et al that used social media posts (Facebook) to solicit public opinion on the use of VR in healthcare [77]. However, within the general population, Keller also found a positive correlation between a person's age and his skepticism of VR's utility.…”
Section: Discussionsupporting
confidence: 85%
“…Our study found that a majority of orthoptists would be willing to incorporate virtual reality as a therapeutic tool for AMD patients if studies prove its effectiveness. This is in concordance with a 2017 survey by Keller et al that used social media posts (Facebook) to solicit public opinion on the use of VR in healthcare [77]. However, within the general population, Keller also found a positive correlation between a person's age and his skepticism of VR's utility.…”
Section: Discussionsupporting
confidence: 85%
“…In line with past research, this study found positive public perceptions towards VR (Keller et al, 2017). However, overall, participants viewed VR as moderately illegitimate ( Figure 2a) and moderately effective (Figure 3), demonstrating a sense of uncertainty.…”
Section: Perceptions Of Effectiveness Legitimacy and Willingness To supporting
confidence: 90%
“…frequencies and percentages of themes and discrete emotions were calculated. Social listening techniques were conducted to capture public perceptions as this approach is able to gather unfiltered public perceptions and avoid the Hawthorne effect where participant may change their behaviour if they are aware they are being studied or may not participate (Keller et al, 2017;McCambridge et al, 2014).…”
Section: Methodsmentioning
confidence: 99%